Identifikasi Dan Kepadatan Sampah Anorganik Di Pantai Ujong Blang Desa Ujong Blang Kecamatan Banda Sakti Kota Lhokseumawe - Yudho Andika; Bengi Pratiwi; Erniati Erniati; Erlangga Erlangga; Imanullah Imanullah (Universitas Teuku Umar, 2023)
The phenomenon of marine debris can cause unrest among the community because it can cause marine pollution that affects the activities of coastal communities. This research was conducted with the aim of knowing the type, density and rate of increase of inorganic waste. The research location is at Ujong Blang Beach, Ujong Blang Village, Banda Sakti District, Lhokseumawe City on November 1-13 2021. The method used is purvosive sampling. The waste sampling technique uses a line transect method drawn from the shoreline along the 50 meters in the direction of the coastline and 10 meters towards the sea, in which there are 3 plots measuring 10x10 m2, the distance between the plots is 10 meters. The waste that is taken is waste that is on the substrate, the observed waste is macro-sized inorganic waste. The results showed that the garbage collected at Ujong Blang Beach, Ujong Blang Village, Banda Sakti District, Lhokseumawe City consisted of 5 types, namely plastic, metal, glass, rubber and clothing. Plastic waste has the highest density value, namely 1.59 items/m2 with a relative density value of 95.22%. The highest density value based on the mass of waste is also found in the type of plastic waste, which is 4.64 gr/m2 and a relative density of 78.64 %. The value of the highest rate of increase in waste was on Sunday with a total of 90.5 pieces of waste and a mass of 437.5 g of waste.